Employee Perception of A Diverse Workforce and Its ‎Effect on Job Satisfaction: The Mediating Role of ‎Organizational Climate in The Hospitality Sector in ‎Kerala - Joseph , Regy; Jegadeeswari , Dr. S (International Journal of Accounting and Economics Studies, 2025)
This research explores the association between a diverse workforce and employee job satisfaction in the hospitality sector. The ‎study is quantitative, and the stratified sampling method is used to ensure the representation of all the departments and ‎employees from the different levels (top, middle, and lower). The study identifies the organizational climate as a mediating ‎variable that is an important factor in job satisfaction. The required data were gathered through a questionnaire, and the analysis was ‎done using SPSS. 223 respondents gave their opinion on the impact of workforce diversity on the satisfaction level of ‎employees. It was found that there is a strong correlation between workforce diversity and employee job satisfaction. When ‎there are individuals with different capabilities, like problem-solving abilities and teamwork, the employee tends to be free ‎from stress. The hotel needs to inculcate this concept in all its properties to boost employee productivity‎.